Analisis Penentuan Komoditas Unggulan Hortikultura di Provinsi Sulawesi Selatan berdasarkan Location Quotient (LQ) dan Shift Share - Aulia Nurul Hikmah; Putra Astaman; Intan Mega Maharani; Dita Rosyita; Yennyka Leilasariyanti (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
The great potential of South Sulawesi Province as a national food hub for horticultural commodities, such as vegetables and fruits, has not been fully realized. This is due to fundamental constraints, including limited product diversification, seasonal and small-scale production, and inefficient marketing channels, which result in low and unstable prices at the farmer level. In addition, policy planning for this sector's development has so far been based on insufficient identification of leading commodities, grounded in data and in-depth analysis at the provincial level. Previous studies have also been limited to analysis at the district or sub-district level, so they cannot be used as an adequate basis for formulating regional horticultural development strategies in South Sulawesi. This study addresses this need by analyzing horticultural commodities using the Location Quotient (LQ) and Shift-Share approaches. The novelty of this study lies in its provincial-level analysis of horticultural commodities (vegetables and fruits) in South Sulawesi. The objectives of this study are (1) to analyze the base sector of horticultural commodities in South Sulawesi Province; (2) to analyze the net growth value of horticultural commodities in South Sulawesi Province; and (3) to analyze leading horticultural commodities in South Sulawesi Province. The LQ analysis using 2024 data successfully identified 16 commodities as the base sector. Then, the Shift Share analysis identified 21 commodities experiencing progressive net growth. By integrating these two results, this study successfully mapped priority commodities. Commodities such as cayenne pepper, shallots, tomatoes, duku, and durian are leading commodities (Quadrant I) with strong production bases and bright growth prospects, making them a top priority in regional agricultural development planning.